The cost of success: Reproductive effort in male southern elephant seals (Mirounga leonina) - Filippo Galimberti; Simona Sanvito; Chiara Braschi; BOITANI, Luigi (Behavioral Ecology and Sociobiology, 2007)
Reproductive effort is a key parameter of life history because it measures the resources allocated to reproduction at the expense of growth and maintenance. Male reproductive effort always had a minor role with respect to female effort both in the development of theories and in field research. Elephant seals are an ideal subject for reproductive effort studies because they fast during the breeding season, splitting the phase of energy acquisition from the phase of energy use for breeding. In this paper, we present results on male reproductive effort (weight loss estimated by photogrammetry) in southern elephant seals (Mirounga leonina), the most dimorphic and polygynous of all mammal species. We show that total reproductive effort increases with age, with no sign of late decrease or senescence. Male reproductive effort in this species depends mostly on behavioral factors, i.e., the success in competition with other males, and the intensity of interaction with females. A large effort results in large gains in both mating success and fertilizations. The large reproductive success that a few males are able to achieve come at a big cost in terms of energy expenditure, but this cost does not seem to affect the likelihood of survival to the following breeding season. © 2007 Springer-Verlag.